A COMPARATIVE STUDY OF POETRY’S STRUCTURE: ‘NIGHT’ BY BLAKE AND ‘SHE WALKS IN BEUATY’ BY BYRON - Ana Rosida (Badan Pengembangan dan Pembinaan Bahasa, 2017)
This research presented the comparative study about the structure in two poetries; they are Night and She Walks in Beauty. It focused the theme, the figure of speech and the imagery. It used the qualitative research. It is analyzed the structure by reading the poetry carefully and giving the note for each line that contains theme, figure of speech and imagery. It used the theory of comparative study and structural approach.The result of this research shows that the poet of those poetries use theme, figure of speech and imagery. There are many kinds of figure of speech and imagery in the poetry. In Night, there are only four figure of speeches namely (a) Simile, (b) Personification, (c) Metaphor and (d) Hyperbole and uses (1) Visual, (2) Auditory, (3) Tactile and (4) Kinesthetic as the imagery. In She Walks in Beauty, Byron uses (a) simile, (b) personification and (c) litotes as figure of speech and its imagery are (1) Visual and (2) Kinesthetic.The poetry Night and She Walks in Beauty appear both differences and similarities with regard to its poet’s writing style. Blake is subjective whereas Byron is objective in writing. Both poets use the nature in different ways to build the theme, the figure of speech and the imagery. Blake uses the nature to describe two contrast place and Byron used the nature to describe a woman character. AbstrakPenelitian ini membahas studi perbandingan tentang struktur dalam dua puisi, yaitu Night dan She Walks in Beauty. Penelitian ini berfokus pada Theme, Figure of Speech dan Imagery. Penelitian ini menggunakan penelitian kualitatif. Pada penelitian ini, struktur dianalisa dengan membaca puisi dengan seksama dan memberikan catatan untuk setiap baris yang berisi Tema, Majas dan Pencitraan. Penelitian ini mengunakan teori Comparative Study dan pendekatan Structural.Hasil penelitian ini menunjukkan bahwa penyair pada kedua puisi ini menggunakan Tema, Majas dan Pencitraan. Ada banyak jenis majas dan pencitraan dalam puisi tersebut. Pada puisi Night, Majas hanya ada empat yaitu (a) Simile, (b) Personification, (c) Metaphor dan (d) Hiperbole dan menggunakan (1) Visual, (2) Auditory, (3) Tictile dan (4) Kinestethic sebagai pencitraan. Pada puisi She Walks in Beauty, Byron menggunakan (a) Simile, (b) Personification dan (c) Litotes sebagai majas dan pencitraannya adalah (1) Visual dan (2) Kinestethic.Puisi Night dan She Walks in Beauty tampak perbedaan dan persamaan yang berkaitan dengan gaya penulisan penyairnya. Blake adalah penyair yang subjektif sedangkan Byron adalah penyair yang objectif dalam menulis. Kedua penyair tersebut menggunakan alam dengan cara yang berbeda untuk membangun Tema, Majas dan Pencitraan. Blake menggunakan alam untuk menggambarkan dua tempat yang dan Byron menggunakan alam untuk menggambarkan karakter wanita.